2014
DOI: 10.1007/s00217-014-2352-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and sensory evaluation of wine matured in oak barrel: effect of oak species involved and toasting process

Abstract: and ellagitannin concentration is related linearly to astringency intensity (R = 0.811, p < 0.001). Wine aged in Slavonia showed characteristics similar and intermediate to those of the same wine aged in French and American oak woods, suggesting that they are suitable for barrel production of quality wine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 37 publications
10
71
0
Order By: Relevance
“…In C wine, Vn, Gua and Eg were present in low levels, in accordance with other authors Gomez Garcia-Carpintero et al, 2012;Chira and Teissedre, 2015) who reported low amounts of wood derived compounds in wines not aged in contact with wood.…”
Section: Volatile Compositionsupporting
confidence: 91%
See 4 more Smart Citations
“…In C wine, Vn, Gua and Eg were present in low levels, in accordance with other authors Gomez Garcia-Carpintero et al, 2012;Chira and Teissedre, 2015) who reported low amounts of wood derived compounds in wines not aged in contact with wood.…”
Section: Volatile Compositionsupporting
confidence: 91%
“…The first group is formed by the wines treated with AC chips and is found in the upper left part of the graph. These wines are characterized by their high Vn, AVn and MGua and low IA and IEg contents, in agreement with the findings of Chira and Teissedre (2015), who also observed that AC wood resulted in high amounts of Vn and AVn in the corresponding wines. The second group is formed by the wines treated with A chips and is found below the first one.…”
Section: Volatile Compositionsupporting
confidence: 90%
See 3 more Smart Citations